ANALISIS GAYA KEPEMIMPINAN TRANSAKSIONAL DAN TRANSFORMASIONAL TERHADAP KOMITMEN ORGANISASI IMPLIKASINYA TERHADAP PELAYANAN MASYARAKAT DESA (Studi Pada Kantor Keuchik Kecamatan Juli Kabupaten Bireuen) - Saifannur, Saifannur; Syaripuddin, Syaripuddin; Sumantri Mangkuwinata, Denny (Ekonomika : Jurnal Ekonomi dan Pembangunan, 2024)
The research aims to analyze the Village Head's leadership, both in transactional and transformational styles as well as his commitment which has implications for village community services. Case study of the District Head Office (Keuchik) of July District, Bireuen Regency. This is descriptive research with an associative type. Based on 179 community samples who were used as resource persons, the results obtained were that (1) employees' perceptions of transactional and transformational leadership styles at the Geuchik Office, Juli District, Bireuen Regency were good in increasing organizational commitment and community service, reaching an average of 80.25%. And commitment to the organization also tends to be good, reaching 79.6%. And activities in community services are in the good category, reaching 80.44%. (2) The results of quantitative data analysis found that there was a direct and indirect influence of transactional and transformational leadership styles on organizational commitment of 38.53% and 41.28%. (3) Simultaneously transactional and transformational leadership styles have a significant contribution to organizational commitment of 73.6. (4) There is a direct and indirect influence of transactional leadership and transformational leadership, respectively 30.16% and 31.8%. (5) Simultaneously transactional leadership style and transformational leadership style have an effect on community service through organizational commitment by 18.81%.